Investigation of cytotoxic and antibacterial activity of methanol extract of callicarpa macrophylla leaves - Mona, Rubaiyat Islam (BRAC Univeristy, 2017)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2016.